Digital Preservation process of image collections: With special reference to public libraries. - Janen, T.; Kupeshan, R.; Arulanantham, S. (Bishop Heber College, 2017)
A public library is a social institution established by law, financed by public fund, open for all without any discrimination, for general and free diffusion of knowledge and information in the community. Also be responsible for preservation and development of cultural and antiquarian heritage of the community. This paper revealed that, digitizing the images from various valuable sources with the metadata standard and develop digital repository for image collections.
Keywords: Digitization; Image Library; Preservation